Risk characteristics of China’s marine disasters and trends since 2000 - Wang, Yebao; Ding, Yana; Geng, Ruiying; Chen, Chuntao (Frontiers in Marine Science, 2023)
Understanding the risk characteristics of marine disasters is of great importance for disaster prevention and mitigation. In this study, we considered four types of marine disasters typical in China, including storm surges, rough seas, harmful algal blooms, and oil spills to identify risk characteristics. Disaster risk was analyzed based on the theory that the marine disaster risk consists of hazard, exposure, and vulnerability. These three factors have been analyzed based on statistical data from a collection of historical documents and official records. The following characteristics were identified. First, the occurrence frequency of storm surges and rough waves has remained stable over the past few decades, but the occurrence frequency of red tides and oil spills has shown a downward trend. Second, storm surges were found to be the main cause of economic losses, while rough seas were the main cause of death. Economic losses and fatalities have shown a downward trend against the backdrop of a growing economy and population. Third, there are clear regional differences in the spatial distribution of all disasters, so it is necessary to formulate disaster prevention and mitigation plans according to the spatial differentiation of risks. Based on the various disaster prevention and mitigation measures taken by the government, this study makes some recommendations for future actions that the government should take from the perspective of risk composition. The risk analysis paradigm for marine disasters provided in this study is expected to be used for future marine disaster prevention and mitigation.